ARE COPEPODS VIABLE OPTIONS AS LIVE FOOD IN AQUACULTURE HATCHERIES? - Wa Iba; Hatim Albasri (Indonesian Aquaculture Journal, 2009)
This present paper overviews the use of copepods in aquaculture. Some culture methods and nutritional values also described to decide whether copepods are viable and reliable to be used as live food in aquaculture hatcheries. Copepods have been known to have higher nutritional value than Artemia and rotifers. In aquaculture, they have been used to fed various species of marine finfish with better results in terms of growth, larval survival and pigmentation compared to some fish larvae fed on other live feeds. However, culturing copepods in intensive systems to harvest high number of copepods is not well established yet due to lack of funding and knowledge. Meanwhile extensive and semi intensive systems are possible to transfer parasites and diseases from wild environment. Furthermore, nutritional value can not be controlled in such systems.